A walk in the maze: variation in Late Jurassic tridactyl dinosaur tracks from the Swiss Jura Mountains (NW Switzerland) - Diego Castanera; Matteo Belvedere; Daniel Marty; Géraldine Paratte; Marielle Lapaire-Cattin; Christel Lovis; Christian A. Meyer (PeerJ, 2018)
Background Minute to medium-sized (footprint length (FL) less than 30 cm) tridactyl dinosaur tracks are the most abundant in the Late Jurassic tracksites of Highway A16 (Reuchenette Formation, Kimmeridgian) in the Jura Mountains (NW Switzerland). During excavations, two morphotypes, one gracile and one robust, were identified in the field. Furthermore, two large-sized theropod ichnospecies (Megalosauripus transjuranicus and Jurabrontes curtedulensis) and an ornithopod-like morphotype (Morphotype II) have recently been described at these sites. Methods The quality of morphological preservation (preservation grade), the depth of the footprint, the shape variation, and the footprint proportions (FL/footprint width (FW) ratio and mesaxony) along the trackways have been analyzed using 3D models and false-color depth maps in order to determine the exact number of small to medium-sized morphotypes present in the tracksites. Results The study of footprints (n = 93) recovered during the excavations has made it possible to identify and characterize the two morphotypes distinguished in the field. The gracile morphotype is mainly characterized by a high FL/FW ratio, high mesaxony, low divarication angles and clear, sharp claw marks, and phalangeal pads (2-3-4). By contrast, the robust morphotype is characterized by a lower FL/FW ratio, weaker mesaxony, slightly higher divarication angles and clear, sharp claw marks (when preserved), whereas the phalangeal pads are not clearly preserved although they might be present. Discussion The analysis does not allow the two morphotypes to be associated within the same morphological continuum. Thus, they cannot be extramorphological variations of similar tracks produced by a single trackmaker. Comparison of the two morphotypes with the larger morphotypes described in the formation (M. transjuranicus, J. curtedulensis, and Morphotype II) and the spatio-temporal relationships of the trackways suggest that the smaller morphotypes cannot reliably be considered as small individuals of any of the larger morphotypes. The morphometric data of some specimens of the robust morphotype (even lower values for the length/width ratio and mesaxony) suggest that more than one ichnotaxon might be represented within the robust morphotype. The features of the gracile morphotype (cf. Kalohipus isp.) are typical of “grallatorid” ichnotaxa with low mesaxony whereas those of the robust morphotype (cf. Therangospodus isp. and Therangospodus? isp.) are reminiscent of Therangospodus pandemicus. This work sheds new light on combining an analysis of variations in footprint morphology through 3D models and false-color depth maps, with the study of possible ontogenetic variations and the identification of small-sized tridactyl ichnotaxa for the description of new dinosaur tracks.